Clinical trials in chronic myeloid leukemia - Saußele, Susanne; Pfirrmann, Markus (Current hematologic malignancy reports, 2012)
The introduction of the tyrosine kinase inhibitor (TKI) imatinib in the treatment of Philadelphia chromosome-positive chronic myeloid leukemia (CML) has substantially improved the outcome of CML patients. Despite the positive results, problems and questions remained. This was the rationale to setup trials for treatment optimization, where imatinib was administered in higher dose and/or in combination with other therapy but where also new and potentially more efficacious second-generation TKI, nilotinib and dasatinib, were investigated. This review summarizes data of recently published first-line studies with the standard treatment imatinib 400 mg as one study arm. Results of randomized comparisons to higher-dose imatinib treatment, nilotinib or dasatinib are discussed. With regard to outcome interpretation, general aspects on statistical issues and endpoint definitions are put into focus. Considering decidedly increased longevity thanks to TKI treatment, future research should include the evaluation of the quality of life (QoL). Relating also to QoL, safe ways of drug discontinuation need to be investigated.
Gesehen am 17.09.2018